Environmental water allocations are insufficient to control an invasive wetland plant: evidence from a highly regulated floodplain wetland. Issue 5 (24th June 2014) - Vivian, Lyndsey M.; Ward, Keith A.; Zwart, Alexander B.; Godfree, Robert C.; Sheppard, Andy
Summary Regulation of the world's rivers and alteration of natural flow regimes have led to the degradation of floodplains and wetlands. Here, we investigate plant–flood interactions in a floodplain wetland to determine whether a return to more natural flooding regimes using environmental water allocations can contribute to restoration from a degraded state. We use detailed field surveys to quantify the effects of flooding on a native rush, Juncus ingens, which has become invasive in floodplain grasslands in south‐eastern Australia. We then apply these results to determine the likelihood of generating the flood regime required to control J. ingens in its new range, considering the regulated nature of the river system. Complete submergence for several months substantially reduced J. ingens stem densities, survival and recovery. However, rhizomes were able to survive, with new stems produced during subsequent partial submergence. Under current regulated conditions, the volume of environmental water needed to cause substantial stem decline, and potentially rhizome death, is extremely large – particularly for tall stems – even when used in conjunction with a natural flood peak. Synthesis and applications. Although repeated submergence events may cause stem decline of the invasive plant Juncus ingens, the present day operational constraints of the regulated river make it difficult to deliver the required volume and depth of water using environmental water allocations. Furthermore, shallow floods may actually provide favourable conditions for growth. This research is particularly relevant for other restoration projects where historical disturbance regimes can only be partially mimicked. Whilst a managed flood regime can be successful in achieving a range of conservation and restoration goals, there may be situations in which river regulation can limit the ability to effectively manage particular species using environmental water allocations alone.